Regulatory choices and commitment: challenges for electricity market regulation in Kosovo - Lars Kumkar (Kiel Institute for World Economics (IfW), 2002)
This paper aims at describing the choices to be made in selecting and implementing a reform model for the electricity industry and to derive some implications for the situation in Kosovo. The paper argues that the appropriate reform model depends on the circumstances in the considered jurisdiction. Especially in small and less developed electricity systems a dilemma may emerge: the technical circumstances suggest the implementation of a model with few competitive elements, whereas political circumstances urge for a competition-oriented model. Hence, especially in small systems, a delicate trade-off emerges that significantly complicates the decisions to be made. This is obviously relevant for Kosovo. An international opening of Kosovo's electricity market may provide a solution to the dilemma. This international opening encompasses a reduction of state sovereignty for electricity regulation and a wide-reaching market opening for private investors and electricity traders.
Keywords: K2; H4; L5; Q4; P3; L9; 330; Power sector; new institutional economics; liberalization; pool; privatization; regulation; restructuring; single buyer; transition; Elektrizitätspolitik; Deregulierung; Außenhandelsliberalisierung; Reform; Neue Institutionenökonomik; Kosovo